Nursing, environment and health conceptions: an ecosystemic approach of the collective health production in the primary care Concepciones de enfermería, salud y ambiente: un enfoque ecosistémico de la producción coletiva de salud en la atención básica Concepções de enfermagem, saúde e ambiente: abordagem ecossistêmica da produção coletiva de saúde na atenção básica - Marta Regina Cezar-Vaz; Ana Luiza Muccillo-Baisch; Jorgana Fernanda de Souza Soares; Alísia Helena Weis; Valdecir Zavarese da Costa; Maria Cristina Flores Soares (Universidade de São Paulo, 2007)
The present study aimed to understand the meanings of the conceptual environment category, produced by nurses acting in the primary health care. A total of 30 nurses participated in the study. Data were collected through semi-directed interviews. The analysis was performed through the thematic method of the empirical meanings, based on the ecosystemic approach of work. The study showed the meanings of environment in the space limits of the human relations, whether they are produced at work, in the family scope or in the general community, in a transversal system that allows relationships of mutual exchange by the human condition itself in the society. Concluding, the development in the nursing area, in an ecosystemic approach of the human health, demands the construction of management strategies integrated to the environment for the promotion of health. The nursing science can be an ally in the construction of healthy and sustainable environments. El presente estudio buscó comprender los significados de la categoría conceptual ambiente establecido por las enfermeras que trabajan en la atención básica. Treinta enfermeras participaron del estudio. Los dados fueron recolectados a través de entrevista semi-dirigida. El análisis realizado a través del método temático de los significados empíricos, fundamentado en el enfoque ecosistémico del trabajo. El estudio mostró los significados del ambiente dentro del límite de espacio para las relaciones humanas, establecidas en el trabajo, en la familia y en la comunidad en general; a través de la sistemática transversal se pudo establecer relaciones de intercambio mutuo entre los seres humanos en la sociedad. Se comprende finalmente que el desarrollo en el campo de la enfermería, en un enfoque ecosistémico, exige la construcción integrada de estrategias de medio ambiente para la promoción de la salud. La ciencia de enfermería puede ser una aliada en la construcción de ambientes saludables y sustentables. O presente estudo procurou compreender os significados da categoria conceitual ambiente, produzidos pelas enfermeiras atuantes em atenção básica. Trinta enfermeiras participaram do estudo. Os dados foram obtidos por entrevista semidirigida. A análise foi realizada pelo método temático dos significados empíricos, ancorado na abordagem ecossistêmica do trabalho. O estudo mostrou os significados de ambiente nos limites do espaço das relações humanas, sejam essas produzidas no trabalho, na abrangência familiar e da comunidade em geral, em uma sistemática transversal que viabiliza relações de troca mútua pela própria condição humana na sociedade. A compreensão final é que o desenvolvimento no campo da enfermagem, numa abordagem ecossistêmica da saúde humana, exige a construção de estratégicas integradas do meio ambiente para a promoção da saúde. A ciência da enfermagem pode ser um aliado na construção de ambientes saudáveis e sustentáveis.